Analysis of Islamic Law on Cooperation Agreements in Micro, Small and Medium Enterprises - Reliyanti, Reliyanti; Kurniawan, Kurniawan (Zabags Qu Publish, 2024)
The cooperation contract (akad) in Micro, Small, and Medium Enterprises (MSMEs) plays an important role in boosting the community's economy. From the perspective of Islamic law, cooperation contracts must adhere to Sharia principles such as justice, honesty, and transparency. This study aims to analyze the compliance of cooperation contracts in MSMEs with Islamic law, focusing on contracts such as mudharabah, musyarakah, and wakalah. The research method used is a literature study and normative juridical analysis. The findings show that most cooperation contracts in MSMEs comply with Islamic law principles, although challenges remain in implementation, particularly regarding transparency and profit-sharing. This study provides recommendations to enhance MSME actors' understanding of Sharia contracts to increase business blessings. Additionally, the study highlights the importance of Sharia supervision in ensuring that contracts remain within the framework of Islamic law. It was found that continuous education on Sharia contracts can minimize the risk of non-compliance in business practices. The research also emphasizes the need for local regulatory adaptation to align with Sharia principles. The results are expected to serve as a reference for policymakers in strengthening the Sharia-based legal framework for MSMEs. Finally, this study asserts that the success of Sharia cooperation contracts is measured not only by economic gains but also by social blessings.